Interaction of fetuin-A with obesity related insulin resistance and diabetes mellitus - Öner-İyidoğan Yıldız; Koçak Hikmet (Türk Biyokimya Dergisi)
Fetuin-A (FetA) is a glycoprotein primarily synthesized in hepatocytes, but recent studies have demonstrated that it is also synthesized in adipose tissue, classifying it as both a hepatokine and an adipokine. FetA has been shown to play a role in the regulation of glucose and lipid metabolism, thereby controlling overall body homeostasis. Elevated serum FetA levels have been reported in obesity, and this increase has been associated with insulin resistance (IR) and type 2 diabetes mellitus (T2DM). Therefore, investigating the molecular mechanisms underlying the variations of FetA in obesity and obesity-related metabolic diseases is crucial for the development of preventive strategies. Studies examining the molecular pathways involved in the relationship between FetA, adipose tissue, IR, and T2DM have shown that deviations in the expression of transcription factors such as nuclear factor erythroid-related factor 2 (Nrf2), nuclear factor kappa B (NF-κB), and peroxisome proliferator-activated receptor γ (PPARγ) in pancreatic, adipose, and liver cells contribute to the increase in FetA and the development of IR and/or T2DM. Consequently, future studies aimed at suppressing transcription factors in the signaling pathways that increase FetA expression, and identifying new agents that can regulate FetA secretion, could be therapeutically beneficial in treating obesity and obesity-related complications.